Halimaw - Molina, Russell; Joson, Rommel; Tamayo, Faith (Quezon City LG & M Corporation, 2013)
"There's a monster at Empoy's school. Everyday Empoy dreads getting up and going to school because the shape-shifting monster lurks the vast ground of their campus. Even in his dreams, this fearsome, fire-breathing monster haunts him. Empoy lives in so much fear that one day, he becomes sick and can't go to school. Young and old alike can learn something from Halimaw, a story about facing monster and finding the fighter within."
Ages 7-13 y.o.
Text in Filipino and English.
Keywords: Children's stories, Philippine (English)